RAINWATER HARVESTING PLANNING AS AN ALTERNATIVE FOR CLEAN WATER SUPPLY IN PUBLIC FACILITIES IN SEPAKU DISTRICT: A STUDY OF SUPPLY POTENTIAL USING PROBABILITY METHODS - Ika Meicahayanti; Elvina Amalia Putri; Mardewi Jamal; Dharwati Pratama Sari; Budi Haryanto; Tamrin Tamrin; Agus Maryono; Arno Adi Kuntoro (Jurnal Teknologi Lingkungan UNMUL, 2026)
The clean water supply in Sepaku District covers only 15.27% of the total water demand. Efforts to utilise rainwater as an alternative source are necessary due to this region has high rainfall. The study aims to analyse the potential of rainwater discharge and design a Rainwater Harvesting (RWH) system to support clean water provision. The analysis was conducted on rainfall data using probability methods, calculations of potential rainwater discharge, and sizing of the RWH system components. The rainwater potential was calculated based on reliable rainfall, roof area, runoff coefficient, and first-flush volume. The RWH system design included determining suitable storage tank capacity, gutter specifications, and first-flush pipe dimensions. The results of this study indicate that the potential for rainwater harvesting and the design of the Rainwater Harvesting (RWH) system vary across buildings, depending on roof catchment area and rainwater availability. The rainwater potential discharge varies accross locations, ranging from 109.3 to 434 m3/year, influenced by differences in roof area as catchment area. The RWH system planned consists of storage tank capacities of 2.2, 3.2, and 7.5 m³, horizontal pipes of 100–150 mm, vertical pipes of 75–125 mm, and first-flush pipes of 6 inches or 10 inches with a height of 1.45–3.38 m. This design is adjusted to the rainwater potential that can be applied in each building and is expected to become an alternative clean water supply.